Heat transfer and thermal conductivity enhancement using graphene nanofluid: a review - Hilo, Ali; Abu Talib, Abd Rahim; Nfawa, Sadeq Rashid; Sultan, Mohamed Thariq Hameed; Abdul Hamid, Mohd Faisal; Bheekhun, M.I. Nadiir (Akademia Baru Publishing, 2019)
Among other nanoparticles, higher thermal conductivity can be found in Carbon nanostructures due to the low density and intrinsic thermal conductivity in comparison with metals or metal oxides. This paper has reviewed the results of different experiments that were done to examine the heat transfer capabilities of graphene nanofluids. An overview summary of the latest graphene nanofluid’s preparation methods in addition to some features that effect on the thermal conductivity such as viscosity, concentration, particles size and temperature has been provided. Furthermore, a critical review has been given to the convective heat transfer performances of graphene nanofluids. The paper showed that a significant result is found in using graphene nanofluids as a working fluid through tube channel to enhance heat transfer. In regard to the literature there is no study has been done on the influence of graphene nanofluids in facing step and corrugated.